Global Problem of Hospital Detention Practices - Krisna Handayani; Tyas C. Sijbranda; Maurits A. Westenberg; Nuria Rossell; Mei N. Sitaresmi; Gertjan JL Kaspers; Saskia Mostert (Kerman University of Medical Sciences, 2020)
Although an official definition by the World Health Organization (WHO) or any other authority is currently lacking, hospital detention practices (HDP) can be described as: "refusing release of either living patients after medical discharge is clinically indicated or refusing release of bodies of deceased patients if families are unable to pay their hospital bills." Reports of HDP are very scarce and lack consistent terminology. Consequently, the problem's scale is unknown. This study aimed to find evidence of HDP worldwide, explore characteristics of HDP reports, and compare countries with or without reports. PubMed and Google were examined for relevant English, Spanish, and French publications up to January 2019. Of 195 countries, HDP reports were found in 46 countries (24%) in Africa, Asia, South-America, Europe, and North-America. Most reports were published by journalists in newspapers. In most countries reports concern living adults and children who are imprisoned in public hospitals. A majority (52%) of reports were of individuals detained for at least a month. Almost all countries, with or without HDP reports, have signed the Universal Declaration of Human Rights. Countries with reported HDP have larger population size (P < .001), worse Corruption Perception Index score (P = .025), higher out-of-pocket expenditure (P = .024), lower Universal Health Coverage Index score (P = .015), and worse Press Freedom Index score (P = .012). We conclude that HDP are more widespread than currently acknowledged. Urgent intervention by stakeholders is required to stop HDP.